2023
DOI: 10.3390/biom13030440
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of microRNA Expression Profile in Roots and Leaves of Three Wheat Cultivars under Water and Drought Conditions

Abstract: Wheat is one of the most important food sources on Earth. MicroRNAs (miRNAs) play important roles in wheat productivity. To identify wheat miRNAs as well as their expression profiles under drought condition, we constructed and sequenced small RNA (sRNA) libraries from the leaves and roots of three wheat cultivars (Kukri, RAC875 and Excalibur) under water and drought conditions. A total of 636 known miRNAs and 294 novel miRNAs were identified, of which 34 miRNAs were tissue- or cultivar-specific. Among these, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Small interfering RNAs (siRNAs) are a predominant class of small RNAs (sRNAs) in plants [190,191]. Alongside microRNAs (miRNAs), they play vital roles in epigenetic regulatory pathways and modulate the expression of genes associated with development and stress tolerance [192,193]. Using deep sequencing technology, Ma et al [194] analyzed two wheat genotypes with contrasting stress tolerance and identified 367 differentially expressed miRNAs in leaves under drought stress.…”
Section: Genotype-dependent Epigenetic Responsesmentioning
confidence: 99%
“…Small interfering RNAs (siRNAs) are a predominant class of small RNAs (sRNAs) in plants [190,191]. Alongside microRNAs (miRNAs), they play vital roles in epigenetic regulatory pathways and modulate the expression of genes associated with development and stress tolerance [192,193]. Using deep sequencing technology, Ma et al [194] analyzed two wheat genotypes with contrasting stress tolerance and identified 367 differentially expressed miRNAs in leaves under drought stress.…”
Section: Genotype-dependent Epigenetic Responsesmentioning
confidence: 99%